T -dual cosmological solutions in double field theory. II. - Bernardo, Heliudson [UNESP]; Brandenberger, Robert; Franzmann, Guilherme (American Physical Society (APS), 2019)
In this paper we present cosmological solutions of double field theory in the supergravity frame and in the winding frame which are related via T-duality. In particular, we show that the solutions can be viewed without the need of complexifying the cosmological scale factor.